Analytical Modeling in Deformation Analysis of Interference-Fit Structures. (May 2016) - Aleksandrova, Nelli
Abstract: Local analysis of bearing stresses and initiation of failure at fastener-hole location in interference-fit structures is crucial for achieving their optimal structural design and reliable service conditions. To this end, analytical research devoted to strain analysis of double-shear riveted or bolted joints is performed. The decohesive carrying capacity criterion based on the radial strains is applied and discussed. The material of the plate is considered to be elastic-perfectly-plastic obeying the Huber–Mises–Hencky yield criterion while the bolt is considered to be elastic. Due to the singularities in the radial strains and displacement at the fastener/plate interface, the problems solved analytically are of great importance for implementation of commercial numerical codes. Highlights: Analytical strain analysis of interference-fit structures is performed. Decohesive carrying capacity criterion based on the radial strains is applied and discussed. Limit load carrying capacity is estimated for practical engineering purposes. Interference and expansion ratios are adjusted for practical engineering applications.